El consenso de Washington y el foro de Sao Paulo como modeladores de la agenda política latinoamericana - Cobo Robayo, Jeaneth Fernanda (2017)
The present research paper focuses on analyzing how two key ideological for a influence and shape the political agenda of the countries in the region of Latin America, particularly the Washington Consensus that shaped politics between 1989 and year 2000 and the Sao Paulo Forum that took place in 1990. This paper discusses the before mentioned fora and the influence they had in the decade of the 90s, specifically emerging from the Washington Consensus and the period of the Rafael Correa administration as part of the Sao Paulo Forum. This paper does not only focus on their importance for the academy but also for its importance for the Ecuadorian society because of the impact both forums had in the political and social arena. As all of these can be seen the situation that Ecuador and Latin America are living today. There are two sides for the application of these forums. There is for one side the application of liberalism through the Washington Consensus, and another side related to the Sao Paulo Forum, which has a great influence in the Ecuadorian politics nowadays. In this paper, I first describe both ideological fora and, second, draw on this description for a comparative analysis, arguing the application of these forums in the history of Ecuador. Finally, I conclude that both fora seek the same sort of stability, despite ideological differences and their failed political application promoted with their creation.